Reframing Leadership - Matthew Sowcik; Hannah S. Carter; Valerie McKee (EDIS)
Effective leadership is essential in the businesses where we work, the institutions where we learn and in the communities where we live. Our own leadership is a product of how we see the world. The article looks at Bolman and Deal's book Reframing Organizations and the different frames to address organizational issues and leadership.